A novel difficulty scoring system for laparoscopic colorectal cancer surgery for appropriate case selection according to master - Takashimizu, Kiyoharu; Otsuka, Koki; Yaegashi, Mizunori; Sasaki, Tomoko; Sasaki, Akira; Nakamura, Yuya; Ariyoshi, Yu; Hatanaka, Tomoki; Takahash, Fumiaki (Journal of Iwate Medical Assiociation, 2023)
Mastering laparoscopic colorectal cancer surgery involves a learning curve. Inexperienced surgeons requireappropriate case selection. Nonetheless, there are few indicators for predicting the difficulty of laparoscopic colorectal cancer surgery. We established a difficulty scoring system to facilitate appropriate case selection during the learning curve for laparoscopic colorectal cancer surgery until mastery is achieved.We reviewed 1,390 laparoscopic colorectal cancer surgery cases performed at our hospital. Surgical duration was used as an index of surgical difficulty. Factors related to surgical difficulty were identified using a multivariate analysis and were scored using a linear regression analysis.Overall, 889 patients were included in the analysis. Sex, body mass index 〉 25 kg/m2, and tumor location were factors that best defined surgical difficulty. The difficulty was determined by the sum of prolonged surgical duration predicted by these three factors. Surgical duration and hospital stay were longer, blood loss was greater, and complications were more common in the high difficulty group than in the low and medium difficulty groups. The developed scoring systemshowed high reliability in ten-fold cross-validation.The scoring model we developed can predict surgical difficulty for typical laparoscopic colorectal cancer surgery and may be useful in selecting appropriate surgical cases for inexperienced surgeons.